IMPROVING LEARNING MOTIVATION THROUGH INFORMATION TECHNOLOGY-ASSISTED ACTIVE LEARNING IMPLEMENTATION TOWARD BIOLOGY - SUGIYONO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The low learning motivation of students of SMK (Vocational High School) Cangkringan on Biology subjects raises concerns for the researcher. Students with low learning motivation immediately stop trying to learn every time they face learning difficulties or when facing exams. Based on this, the purpose of this Classroom Action Research is to increase the learning motivation of class XI APP SMK Cangkringan in Biology by implementing technology information assisted active learning. The study was used as a Classroom Action Research (CAR) procedure. The CAR was carried out in two cycles, focus on observation of the activeness of students during the learning process. The subjects of this study were the biology teacher who also acted as a researcher and all students of class XI APP SMK Cangkringan. There are 29 students in class XI APP 3, consisting of 23 females and 6 males. The results showed that the implementation of information technology-assisted active learning can increase the learning motivation of class XI APP students towards Biology subjects, this is indicated by the level of student activeness in all behaviors observed reaching the criteria set by the researcher, which is 85%.